Interaction Between a Lateritic Soil and a Non-woven Geotextile in Different Moisture Conditions - Marques, Gabriel Steluti; Lins da Silva, Jefferson (Frontiers in Built Environment, 2020)
This work evaluates the increase in stiffness provided by the variation of moisture content (matrix suction) and the grain size structure at the interface between a cohesive tropical soil (lateritic clay) and a nonwoven geotextile. For this purpose, monotonic pullout tests with soil suction monitoring were performed on small-sized equipment under three scenarios ("O" Optimum, "D" Dry and "DP" Dry Post-Compaction) and two vertical pressures (14 and 28 kPa). The Dry Post-Compaction tests were conducted with the same matrix suction of the Dry tests. The monotonic pullout tests evaluated the soil-geosynthetic interaction under constant displacement to calculate the apparent confined stiffness of the geosynthetic (Jc). The Wide Width Tensile tests were conducted to assess the unconfined stiffness of the nonwoven geotextile (Jn). The Dry scenario, compacted with higher compaction energy than the others and, consequently, altering its grain size structure, presented the best performance. This indicates that other parameters besides the suction may be influencing the interaction between the soil and the non-woven geotextile. Even under small vertical pressures, the apparent confined stiffness improves considerably compared to the unconfined stiffness. This indicates that the use of the unconfined stiffness obtained by index tests may be a conservative measure in paving projects.